PENGARUH HARGA, KUALITAS LAYANAN, CITRA PERUSAHAAN, DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN SICEPAT - Daniel Joel Immanuel Kairupan; Irvansyah, Fajar Eggi (Jurnal Ekonomi Dan Bisnis, 2022)
This study was conducted to determine the effect of price, service quality, corporate image, and customer satisfaction on Sicepat customer loyalty. This study uses the descriptive quantitative method. The sample in this study amounted to 102 respondents with a sampling method using purposive random sampling. Collecting respondent data using google form media with the questionnaire method. Analysis of the study data using the SmartPLS 3.0 test tool with the SEM (Structural Equation Modeling) method. The results of this study indicate that price has a significant positive effect on customer satisfaction, service quality has a significantly positive effect on customer satisfaction, company image has a significantly positive effect on customer satisfaction, and customer satisfaction has a significant positive effect on customer loyalty.